Erosion Studies on Traditional Tillage System in Humid Coastal Region of South South Nigeria - Effiom E. Oku; M.N. Armon (Journal of Soil and Water Conservation, 2022)
The field experiment was conducted on Ultisols in the humid forest region of South South Nigeria. The traditional tillage (mounds, holes, trenches and ridges) was laid in a randomized complete block design with four treatments replicated four times. The main thrust was to investigate the effect of traditional tillage on runoff, soil loss, water infiltration and weed infestation when seedbeds are prepared and left bare or planting delayed. There was significant difference in runoff and soil loss with runoff in the following order: mounds> ridges > holes > trenches > ridges. The trend for soil loss was mounds > holes >ridges > trenches. There were no significant differences in infiltration and weed infestation between the tillage systems. Regression and correlation analysis showed a linear relationship the r and R-2 (correlation coefficient and determination were used to test how close the variables are to being linear. Trenches(r = 0.34, R-2= 0.61) mounds (r = 0.89, R-2= 0.95), ridges (r = 0.73, R-2= 0.86) and holes(r = 0.89, R-2= 0.94). Mounds tillage should be discouraged where there is lack of soil and water conservation technique.